Análise multielementar pela técnica de fluorescência de raios-X de amostras de cólon de roedores com colite e tratados com prednisolona - Silva, Káthia Takeda da [UNESP] (2014)
Ulcerative colitis is part of a group of Inflammatory Bowel Disease (IBD) and is characterized by dysfunction of mucosal T cells, abnormal cell inflammation and cytokine production that result in damage to the mucosa of the colon. IBD affects a large portion of the world population, with a higher prevalence in developed countries, affecting about 1.4 million people in the United States and 2.2 million in Europe. In Brazil, the available data are restricted due to diagnostic difficulties and the small number of samples, but it can be stated that the number of cases in the country is increasing. Although there are several studies, the cause of ulcerative colitis is until now unknown. In this sense, the contribution of this work in clarifying this issue is focused on the study of the multielemental composition of the colon tissues from animals with induced ulcerative colitis. We studied samples of rodent colon tissues in three situations: healthy tissue, tissue with induced colitis without pre-treatment and tissue with induced colitis and pre-treated with prednisolone, one of the medications most applied in ulcerative colitis treatment. For the analysis, we used the non-destructive analytical method of X-ray fluorescence by total reflection (TXRF) realized in line D09B - XRF at the Brazilian Synchrotron Light Laboratory - LNLS/CNPEM, Campinas- SP. It was possible to determine the concentrations of P, S , Cl, K, Ca , Ti , Cr, Mn, Fe , Ni , Cu, Zn, Se , Br and Rb elements from the intensity of the corresponding Kα1 lines, by using Ga as internal standard. The corresponding Pearson correlations between the concentrations of the elements were also determined. In this analysis, although the samples have different correlations between P and S, Ca and Ti elements in the different groups, there is no data in the literature to confirm this relation of this elements ...